Physicochemical quality evaluation and drying characteristics of nutmeg (Myristica fragrans) dried in a solar tunnel dryer with biomass backup: Quality evaluation of nutmeg dried in solar tunnel - Jayashree, E; Joseph, Desmond (Journal of Spices and Aromatic Crops, 2022)
Experiments on drying of nutmeg was performed in a solar tunnel dryer with biomass back up and in a mechanical dryer under three varying temperatures of 45OC, 5OC and 55OC. Drying of nutmeg in solar tunnel dryer was completed in 147 h, while in a mechanical dryer, drying was completed in 105 h, 102 h and 78 h at drying temperatures of 45OC, 50OC and 55OC, respectively. Solar tunnel dried nutmeg had maximum physical quality retention of bulk density (484.88 kg m-3) and kernel recovery (70.63%) whereas dry recovery of nut (61.88%) and shell recovery (31.55%) were maximum in mechanically dried samples at 55OC and 45OC respectively. Secondary metabolites like essential oil (10.67%) and oleoresin (23.25%) were higher in mechanically dried nutmeg at a drying temperature of 45OC. Volatile oil constituents like β-pinene, safrole, terpineol, γ-terpinene, α-thujene, α-terpinene and myristicin content were highest in solar tunnel dried nutmeg.